A Description of MMPI-2-RF Profile of Eleven Boko Haram Terrorists - Temitope Folashade Aroyewun; Helen Osinowo; Asma Perveen; Khadijah Aroyewun-Adekomaiya (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2023)
Nigeria, the largest country on the continent of Africa, has been fighting wars with the proclaimed terrorist group Boko Haram. Currently, Boko Haram has between 1,500 and 2,000 fighters; most documentation about them is either a position paper or a situation review. There is scanty data on the personality and psychological assessment of Boko Haram terrorists using a standardized self-report inventory. Hence, this study aims to describe and explore the profile of the Boko Haram suspects on all the scales of the Minnesota Multiphasic Personality Inventory-2-Restructured Form. Eleven respondents were purposefully recruited because they were the only ones incarcerated at the ‘Kiri-kiri’ Prison facility at the time of this research. Their scores on the inventory were descriptively analyzed. More of these terrorists endorsed significant scores or symptoms of emotional/internalizing dysfunction (EID), somatic complaints (RC1), antisocial behavior (RC4), ideas of persecution (RC6), gastrointestinal complaints (GIC), neurological complaints (NUC), suicidal/death ideation (SUI), anxiety (AXY), shyness (SHY), and disaffiliativeness (DSF), while elevated scores or severe symptoms were reported on stress/worry (STW) and psychoticism (PSYC-r). This research provides personality and psychological assessments of Boko Haram terrorists for the first time using MMPI-2-RF, though it is limited by sample size. Therefore, a larger sample size may be needed for further studies and the ability to make inferences and generalizations.